2022
DOI: 10.1371/journal.pcbi.1010519
|View full text |Cite
|
Sign up to set email alerts
|

Radical triads, not pairs, may explain effects of hypomagnetic fields on neurogenesis

Abstract: Adult hippocampal neurogenesis and hippocampus-dependent cognition in mice have been found to be adversely affected by hypomagnetic field exposure. The effect concurred with a reduction of reactive oxygen species in the absence of the geomagnetic field. A recent theoretical study suggests a mechanistic interpretation of this phenomenon in the framework of the Radical Pair Mechanism. According to this model, a flavin-superoxide radical pair, born in the singlet spin configuration, undergoes magnetic field-depen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Kattnig et al have proposed that fast spin relaxation of the O -2 can be dealt with by involving a third scavenger radical [66][67][68]. Babcock et al [69] have also suggested that radical scavenging could resolve the challenge posed by electron-electron dipolar interactions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Kattnig et al have proposed that fast spin relaxation of the O -2 can be dealt with by involving a third scavenger radical [66][67][68]. Babcock et al [69] have also suggested that radical scavenging could resolve the challenge posed by electron-electron dipolar interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Given a suitable choice of scavenger radical, we have shown that such a radical triad model can explain the observed effects (See the supporting information). Because of the fast spin relaxation of superoxide, no magnetic effect is expected for the substitution of 16 O with 17 O [68] in this scenario.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should also be noted that an extended version of the radical pair mechanism, the radical triad mechanism [49][50][51], has been proposed as an explanation for weak magnetic field effects. Radical triads may provide more sensitivity and circumvent issues such as weakening effects from dipolar interactions and fast spin relaxation of superoxide.…”
Section: Figurementioning
confidence: 99%